The INFLUENCE OF PARENTS' SINGING HABITS ON CHILDREN'S ABILITY TO PRODUCE CHURCH CHOIR VOCAL HARMONIES AUTODIDACTICALLY (FEELING) - Branckly Egbert Picanussa; Jermias Hartes Van HArling; Paolo Fabris; Ketrina Tiwery Tiwery; Fridolin L Muskitta; Pravasta B Maulany; Ronaldo B Alfons; Cleopatrik Teyuhayo; Gerrard R Maail (Jurnal Penelitian Musik, 2026)
The paradigmatic change in arts globally and the strengthening of awareness regarding the relationship between arts and cultural plurality in global life have given rise to a contemporary discourse, namely the legitimacy of Ambon as a world music city. The question that needs to be reflected on is how much musical ability the people of Maluku, especially the city of Ambon, have as an asset to make Ambon a world music city. This study aims to find the musical skills of the people of Maluku with a focus on testing the influence of parents' musical background on children's abilities in creating vocal harmony of church choirs autodidactically (constructing vocal harmony of church choir autodidactically feeling). The theory used in this study musical ability according to Sloboda-Juslin and Bordieu. The research approach used is quantitative with multiple regression analysis design. The data collection technique used a questionnaire, the data analysis technique used multiple linear regression. The results of the study found that the ability to produce vocal harmony division (constructing vocal harmony of church choir autodidactically / feeling) is influenced by the musical background of parents who are natural abilities. This is indicated by the multiple linear regression test which states there is an influence of 30%. The division of voices by feeling is not a matter of the accuracy of sound construction based on scientific principles but what is needed is to avoid out of tune which in musical terms is "fals"